Enhancing Performance Through Work-Life Balance and Work Engagement: A Systematic Review in the Manufacturing Sector - M. Romanda Akbar (International Journal of Economics, Business Management and Accounting (IJEBMA), 2026)
This study systematically reviews the empirical and conceptual literature to examine how Work-Life Balance (WLB) and Work Engagement (WE) collectively affect employee performance in the manufacturing sector. Using the PRISMA method, nineteen relevant studies published between 2020 and 2025 were analyzed from the Scopus, Emerald, and Google Scholar databases. The research findings revealed that WLB contributes positively to employee performance by reducing stress, increasing satisfaction, and maintaining productivity, while WE mediate these relationships through increased motivation, enthusiasm, and dedication. This review highlights that integrating flexible work arrangements, psychological development programs, and supportive supervision can optimize WLB and WE outcomes. Furthermore, the implementation of environmentally friendly human resource management practices strengthens sustainable engagement and performance. Despite having positive relationships, variations across cultural and industrial contexts demonstrate the need for longitudinal and experimental research. The study provides theoretical insights into the human factors that drive manufacturing excellence and practical recommendations for organizations to design integrated strategies that improve sustainable performance.